1991
DOI: 10.2466/pr0.1991.68.1.3
|View full text |Cite
|
Sign up to set email alerts
|

The Primary Personality Factors of Hawaiian, Middle Adolescents

Abstract: To determine whether the primary personality factors of Hawaiian, middle adolescents were the same as those Cattell postulated in 1970, for adolescents on the mainland of the United States, and in 1974 for adolescents in Germany, a personality questionnaire representing those factors completed by 694 Hawaiian, middle adolescents (M age = 15.9 yr.) was factor analyzed. Despite the analysis adhering closely to the recommendations of Cattell stated in 1973 and 1978, the eight factors derived are not the set of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Yet, it is necessary for future work to consider that significant etiological and measurement differences most likely exist between middle-aged adults and 17-year-old adolescents that are not fully appreciated at the level of lifetime diagnosis. More sophisticated work needs to be done, perhaps by comparing scores on other, more normal-range and continuous measures (e.g., alcohol consumption), or through the development of novel instruments to assess the latent EXT construct (Krueger, Markon, Patrick, Benning, & Kramer, 2007), in order to increase variance in the measures and power to detect population differences (Grove, 1991; Markon, Chmielewski, & Miller, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, it is necessary for future work to consider that significant etiological and measurement differences most likely exist between middle-aged adults and 17-year-old adolescents that are not fully appreciated at the level of lifetime diagnosis. More sophisticated work needs to be done, perhaps by comparing scores on other, more normal-range and continuous measures (e.g., alcohol consumption), or through the development of novel instruments to assess the latent EXT construct (Krueger, Markon, Patrick, Benning, & Kramer, 2007), in order to increase variance in the measures and power to detect population differences (Grove, 1991; Markon, Chmielewski, & Miller, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Conceptualizing and measuring EXT as a continuous phenotypic trait is advantageous for genetic research for a variety reasons. First, latent traits, relative to discrete diagnostic entities, offer increased statistical power, for example, to detect genetic/environmental associations or to make predictions (Almasy and Blangero, 2000; Grove, 1991). Second, external correlates may be relevant only for shared etiological processes, as opposed to specific etiology.…”
mentioning
confidence: 99%
“…Uehara, Takeuchi, and Smukler (1994) have shown that combining ethnic groups with differing historical, social, and cultural backgrounds can foster erroneous conclusions. Psychological instruments may not retain validity when used across cultures (Campbell, 1991(Campbell, , 1992Takeuchi, Kuo, Kim, & Leaf, 1989).…”
Section: Introductionmentioning
confidence: 99%